(untitled) - Becklin, Karonne J. (Lake Forest, Ill., 2003)
Text/workbook with concept-based objectives correlating to healthcare industry competencies. Features updated terminology, compliance tips, internet projects, and computer-based applications. CD contains word files for forms, letterheads, and projects, and the disk contains data for MediSoft projects. Working papers provide applications for text activities. Softcover
Keywords: Medical offices,Medical Secretaries,Office Management,Practice Management, Medical,Medical assistants; Management